Prevalence of Bovine Fasciolosis,Financial Losses and Risk Factors Associated with the Disease in Lira and Gulu Districts, Northern Uganda - Ogwal, Anthony; Okello, Daniel Micheal; Aliro, Tony; Owiny, David Okello; Ndyomugyenyi, Elly Kurobuza (John Wiley & Sons Ltd., 2025)
Bovine fasciolosis (BF) is a parasitic disease of cattle that causes significant economic impacts to cattle farmers. The physical loses include weight loss, drop in productivity, liver condemnation and mortalities. Tis study assessed the prevalence, financial losses and risk factors associated with the disease in Lira and Gulu Districts, northern Uganda. A cross-sectional study of 720 slaughter cattle from the abattoirs was conducted by macroscopic examination of the animals and carcasses during routine slaughter. In the farms, 120 rectal faecal samples were taken to a laboratory for Fasciola egg detection by simple microscopy, while risk factors were assessed by administering a questionnaire to farm owners. Prevalence of BF was highest (38%) within cattle in the age group of 1–3years and lowest (18%) in those over 5years. The overall BF prevalence was 48% and 26% by postmortem examination and coprology, respectively. The cattle body condition had a significant association (p<0.01) with prevalence of BF, in which emaciated cattle were most affected (59%), while fat ones had the least prevalence (15%). The annual financial loss due to BF infection was USD 89,099. The major risk factors associated with the disease at the farm level were communal grazing in swampy areas (82%) and watering cattle in swamps (71%). Farms where the source of drinking water was swamp water had higher chances (p<0.05) of their cattle having BF. An integrated approach using routine deworming programs, improvement of cattle management practices and control of snail intermediate hosts is recommended to effectively control the spread of BF.